2022
DOI: 10.3390/ijerph19105846
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Dependence from Different E-Cigarette Devices and Combustible Cigarettes among US Adolescent and Young Adult Users

Abstract: E-cigarettes, the most popular tobacco product among adolescents, vary widely in design and nicotine composition; thus, different devices may have different addictive potential. However, few studies examine levels of nicotine dependence across devices among adolescent and young adult (AYA) e-cigarette users. To assess the extent of nicotine dependence among US AYA (ages 13–24) by e-cigarette device type, we conducted a large, national, cross-sectional survey (n = 4351) and used the Hooked on Nicotine Checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…The findings showed that nearly 9 in 10 of the adolescents had a high nicotine dependence from e-cigarettes. This finding was consistent with a study by Lin et al 29 that found high nicotine dependence among most adolescents and young adult e-cigarette users. Nearly a third of the adolescents in our data screened positive for depression and 13.1% reported moderately severe or severe depression.…”
Section: Discussionsupporting
confidence: 93%
“…The findings showed that nearly 9 in 10 of the adolescents had a high nicotine dependence from e-cigarettes. This finding was consistent with a study by Lin et al 29 that found high nicotine dependence among most adolescents and young adult e-cigarette users. Nearly a third of the adolescents in our data screened positive for depression and 13.1% reported moderately severe or severe depression.…”
Section: Discussionsupporting
confidence: 93%
“…For example, among past 30-day disposable e-cigarette users, approximately one in four 13–20-year-olds, one in five 21–24-year-olds, and one in ten 25–40-year-olds reported using their disposable devices on at least 20 of the previous 30 days. These data make it clear that many recent e-cigarette users are engaging in frequent or even daily use, increasing their risk for nicotine addiction [ 25 , 26 ]. Furthermore, among all past 30-day users, AYAs under 21 were more likely to use disposable and pod/cartridge-based e-cigarettes frequently (i.e., 20 out of 30 days) or daily (i.e., 30 out of 30 days) compared to their older counterparts, highlighting young users as being particularly vulnerable to nicotine dependence and addiction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data make it clear that many recent e-cigarette users are engaging in frequent or even daily use, increasing their risk for nicotine addiction [ 25 , 26 ]. Furthermore, among all past 30-day users, AYAs under 21 were more likely to use disposable and pod/cartridge-based e-cigarettes frequently (i.e., 20 out of 30 days) or daily (i.e., 30 out of 30 days) compared to their older counterparts, highlighting young users as being particularly vulnerable to nicotine dependence and addiction [ 26 ]. These patterns also dispel the notions that young users are primarily experimenting with occasional e-cigarette use and support further policy action to prevent frequent use, which increases the risk of nicotine addiction.…”
Section: Discussionmentioning
confidence: 99%
“…More than five million high school students and more than 1 million middle school students in the United States reported using a tobacco product at least once, according to a 2021 national survey [1]. Among adolescents, tobacco use in its many forms has been linked to nicotine dependence [2], psychiatric disorders [3], and early signs of pulmonary disease [4]. The successful design of tobacco prevention programs is crucial in the fight against tobacco use at a young age.…”
Section: Introductionmentioning
confidence: 99%